The Effect of Formal Education and Adversity Intelligence on Marital Satisfaction on Working Women - Prima Dewi Pratiwi; Nanik Prihartanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Formal education has shaped various types of women in this era of globalization. Formal education has a very decisive role in the development of human potential to the fullest. The low level of education is one of the factors causing poverty and adversity. Through education, people have the opportunity to explore their potential in order to obtain a more decent life. Therefore, because the current workforce is not monopolized by men who have dual roles in addition to being housewives and helping to earn a living. The basis of the large number of women making a living is influenced by the need to survive when their husbands cannot provide for a living and the existence of adversity intelligence that makes working women see opportunities in every difficulty that exists. This study seeks to determine the effect of Formal Education and Adversity Intelligence on the marital satisfaction of working women. The quantitative method was used in this study to conduct the research. The population in the study of women working in the Boyolali area of the city amounted to 500 people. The sampling method used purposive sampling so that the total sample was 170 people. Research findings of formal education have implications for marital satisfaction among working women, where the higher the formal education, the lower the level of marital satisfaction. In terms of adversity intelligence, the lower the level of marital satisfaction, the greater the level of adversity intelligence of working women. Furthermore, there is a 34.7 per cent correlation between formal education and adversity intelligence in the context of working women's marital satisfaction.